The Pre-/Post-Transplant Hepatitis C Antibody Associated with the IL-28B RS8099917 TT Genotype and miRNA-122 Expression May Protect Acute Cellular Rejection After LDLT - King-Wah Chiu; Yu-Cheng Lin; Wei-Feng Li; Kuang-Tzu Huang; Li-Wen Hsu; Chih-Chi Wang (Current Issues in Molecular Biology)
This study aimed to investigate the relationship between the IL-28B SNP rs8099917 genotype, miRNA-122 expression, and the immune mechanism of ACR after LT using anti-HCV antibody calibration. A total of 45 patients with HCV received LT. IL-28B SNP rs8099917 genotyping was used to divide patients into TT and GT groups. The relative expression levels of miRNA-122 were calculated by quantitative PCR. Anti-HCV titers before and after LT were tracked to observe the relationship with ACR. The ACR rates were 27.6% for genotype TT and 62.5% for genotype GT, indicating a significantly higher rate in the GT group compared to the TT group (p = 0.024). In the rs8099917 genotype, TT was significantly associated with higher serum miRNA-122 levels than GT (p < 0.001). The TT group had significantly better outcomes than the GT group (p = 0.005). The Mann–Whitney U test showed significant differences in pre-LT and post-LT anti-HCV titers between the IL-28B genotypes (TT and GT) (p values of 0.006 and 0.027, respectively). These results suggested that the IL-28B rs8099917 genotype TT may play a significant role in modulating immune responses, both in terms of anti-HCV titers and the risk of ACR, possibly mediated through miRNA-122 levels.